Ocorrência de suicídio entre trabalhadores em Região de Fronteira - Côrte, Ivo Valente (2019)
Suicide is a serious public health problem that has increasingly drawn the attention of society and authorities around the world. The occurrence of suicide in rural populations is proportionally higher than in urban areas, and chronic poisoning by pesticides is one of the hypotheses raised to explain this phenomenon. This study aims to analyze the possible relationships between exposure to pesticides and the occurrence of suicide among workers in the Vera Cruz do Oeste and Missal municipalities from 2005 to 2016. It specifically aims to: (1) identify the occurrence of suicide in the Vera Cruz do Oeste and Missal municipalities from 2005 to 2016; (2) analyze the labor history of workers who committed suicide in the Vera Cruz do Oeste and Missal municipalities, identifying possible relationships between exposure to pesticides and suicide and (3) to describe the circumstances of suicide occurrence among workers in the municipalities of Missal and Vera Cruz do Oeste. The research is exploratory and descriptive, and utilizes a mixed method, involving the use of quantitative and qualitative data in an integrated way. The data were obtained from three sources: The Department of Informatics at the Unified Health System, death certificates and in-depth interviews with family members of suicide victims. We used simple descriptive statistics and critical epidemiology proposed by Breilh (2006) for the analysis and interpretation of the data. During the study period, 30 suicides occurred, of which 26 death certificates were analyzed and 16 interviews were carried out, including 8 in Missal and 8 in Vera Cruz do Oeste. Among the results the following data is highlighted: the majority, 87.5%, were male; 75% were between 31 and 60 years old, 56.25% were engaged in agriculture; 75% were married; 81.25% were Catholics; 56.25% lived in rural areas; 81.25% had completed or had not completed elementary school and 81.25% used hanging as a method of self-inflicted death. Alcoholism was the most cited mental health problem in 56.25% of the cases. This same percentage of informants (56.25%) stated that the suicide victims had direct exposure to pesticides throughout their lives, with two cases suffering from severe acute intoxication. The findings do not permit a direct relationship to be established between suicide and exposure to pesticides, however they corroborate with research that evaluated the association between exposure to pesticides and the risk of suicide in rural populations. In addition, they contribute to giving visibility to a problem of small rural towns surrounded by monoculture plantations, which indirectly exposes the entire resident population to pesticides. Attention is also drawn to rethinking about the current model of agricultural production, highlighting the need for an agroecology alternative.